Development of mixed matrix membrane for desulfurization of sulfur rich petroleum stream - Burla, Swathi (My University, 2022)
The presented study focused on the methods of synthesizing the hexagonal boron nitride (h-BN), carbon dots (C-dots) and carbon dot doped boron nitride (CBN) nano materials for applications in dibenzothiophene (DBT) desulfurization. The synthesized materials were characterized using different analytical techniques such as transmission electron microscopy (TEM), scanning electron microscope (SEM), X-ray diffraction (XRD) and fourier transform infra-red (FTIR) to confirm the synthesis of the desired products. H-BN was synthesized using chemical vapor deposition (CVD) and heat treatment furnace (HTF) methods, with CVD producing better h-BN product at 900°C calcination temperature and HTF products forming with high impurities. FTIR analysis of h-BN CVD (900°C) showed two characteristic peaks at 1369 cm-1 and 787cm-1 confirming the formation of h-BN. An extra peak at 3250cm-1 of hydroxyl (-OH) vibration, indicates the presence of small amount of -OH on h-BN on all the products. The -OH peak intensity was decreased with increased calcination temperature, as shown from the FTIR spectra of different h-BN products calcined at 3 different temperatures. The TEM analysis observed several stacked parallel line-like structures (layers) with multiple layered disordered structures of h-BN flakes. The SEM image displayed an un evenly distributed grained powder of h-BN microstructure. XRD peaks of h-BN synthesized via CVD method reveals a strong peak of the crystallographic (002) plane at 2θ = 27.17° with some broadening, indicating low crystalline nature of h-BN. The C-dots were successfully synthesized using hydrothermal carbonization of chitosan raw material in an autoclave. The existence of various functional groups in C-dots was confirmed by the FTIR spectroscopy. TEM images clearly showed a nearly spherical shaped C-dots with diameter of 5-10 nm. XRD analysis showed a broad diffraction peak at 2θ =21.07° indicating the presence of amorphous carbon
A thesis submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg in fulfilment of the requirements for the degree of Doctor of Philosophy, 2022